ANALISIS KINERJA PEGAWAI DI SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) KOTA PONTIANAK - Yusdini Arsih E.21109032 (PublikA, Jurnal Ilmu Administrasi Negara, 2014)
This thesis is intended to provide insight into Analysis Performance Officer at the Secretariat of the Regional Parliament Pontianak which includes performance , expertise , and perilakupegawai . Employee Performance Problems in Analysis is the presence of some employees who lack discipline , work climate or less comfortable working environment in completing the work , and the lack of decisive action from the leaders , in addressing employee issues that may hinder the performance of employees . This study used a descriptive analysis approach , ie research that aim to decipher , explain or describe in depth about the topic research.from findings of the research that analyzes employee performance at the Parliament Secretariat Pontianak be it in work performance , skills and behavior of employees indicate that the three elements this has not been able to provide optimal contribution to the improvement of the performance of employees in the parliament Secretariat Pontianak.Required an increase in the quality of employees' work, in addition to training or Bimtek can be done by more seirngnya leader in providing directives to employees, so that employees feel cared for by the leadership, but it can also do a direct assessment of the leadership to employees, so that employees are more motivated in improving the quality of their work. Also needed improvement work atmosphere by way of employee discipline in the sense of giving direction to employees distract employees who are working. Keyword : Analysis Performance Employee Parliament Secretariat